2017
DOI: 10.1038/s41598-017-04839-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin facilitates West Nile virus neuroinvasion via neutrophil “Trojan horse” transport

Abstract: West Nile virus (WNV) can cause severe human neurological diseases including encephalitis and meningitis. The mechanisms by which WNV enters the central nervous system (CNS) and host-factors that are involved in WNV neuroinvasion are not completely understood. The proinflammatory chemokine osteopontin (OPN) is induced in multiple neuroinflammatory diseases and is responsible for leukocyte recruitment to sites of its expression. In this study, we found that WNV infection induced OPN expression in both human and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 63 publications
1
59
0
Order By: Relevance
“…In addition, clinical data also showed that PMNs were the predominant infiltrating leukocytes into the CNS of patients at the early stage of WNV neuroinvasive disease [145,146]. Our recent results show that WNV-infected neutrophils contribute to the viral burden in the mouse brain, suggesting neutrophils could play a major "Trojan horse" role in transporting WNV into the CNS [78]. However, it is possible that some of the neutrophils were infected after they arrived in the CNS.…”
Section: Wnv Neuroinvasion and Neuropathogenesismentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, clinical data also showed that PMNs were the predominant infiltrating leukocytes into the CNS of patients at the early stage of WNV neuroinvasive disease [145,146]. Our recent results show that WNV-infected neutrophils contribute to the viral burden in the mouse brain, suggesting neutrophils could play a major "Trojan horse" role in transporting WNV into the CNS [78]. However, it is possible that some of the neutrophils were infected after they arrived in the CNS.…”
Section: Wnv Neuroinvasion and Neuropathogenesismentioning
confidence: 75%
“…Neutrophils can serve as reservoirs for WNV replication and dissemination in the early stages of infection but contribute to WNV clearance later in the infection process [77]. In addition, neutrophils have also been documented to facilitate WNV neuroinvasion via "Trojan horse" transport [78,79].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Infection of microvascular pericytes in the brain can induce and/or amplify neuroinflammation caused by JEV infection . Researchers have found that the inflammatory chemokine osteopontin (OPN) can loosen the blood‐brain barrier in mice and promote WNV nerve invasive infection (Figure ) . The study found that interferon (IFN) signalling regulates permeability of the blood‐brain barrier after WNV infection .…”
Section: Possible Mechanisms By Which Flaviviruses Penetrate the Bloomentioning
confidence: 99%
“…There may be additional mechanisms that assist WNV infection of endothelial cells or the choroid plexus epithelium and passively transport the virus to the CNS. WNV infects olfactory nerves and spreads to olfactory bulbs, entering through a “Trojan horse mechanism.” Infected immune cells transport the virus to the CNS, and infected neurons are relayed to other neurons by retrograde transport …”
Section: Possible Mechanisms By Which Flaviviruses Penetrate the Bloomentioning
confidence: 99%
See 1 more Smart Citation